Communication Strategies. - Group, Emerald (Emerald Group Pub., 2004)
Successful communication is vital to any business. According to Emerald author Christopher Connolly, more effective communication is reported as a solution to most life and work problems. But what are managers doing about it?. Communication in business teams continues to be essential for effective teamwork, technical excellence and customer responsiveness.